Regulatory B Cells in Systemic Sclerosis Isolated or Concomitant With Hashimoto Thyroiditis - Capriello, Silvia; Ferrari, Silvia Martina; Gatto, Ilenia; Santaguida, Maria Giulia; Fallahi, Poupak; Antonelli, Alessandro; Mangino, Giorgio; Romeo, Giovanna; Virili, Camilla; Centanni, Marco (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a systemic autoimmune disease in which the gastrointestinal disorders represent a complication in up to 90% of patients. SSc may associate thyroid autoimmune disorders, being Hashimoto’s thyroiditis (HT) the more prevalent worldwide. Previous studies examined the behaviour of Th17 lymphocytes and Breg cells in patients with HT and concomitant autoimmune organ-specific disorders. These immune phenotypes seem to play a significant role in the pathogenesis of both these autoimmune processes but their behaviour when these two disorders coexist has not been described. We analyzed Th17 and Breg (CD24hiCD38hi) cells subsets in fifty subjects (45F/5M; median age=49 years): 18 were healthy donors (HD), 20 had isolated HT, 12 had SSc and 7 of them had both HT and SSc. Breg cells function has been also evaluated by measuring their IL-10 production when stimulated by specific activators. An increased percentage of Th17 lymphocytes characterized HT patients as compared to both HD and whole group of SSc patients (p=0.0018). On the contrary, the percentage of unstimulated Breg cells in SSc patients was higher (p=0.0260), either associated or not to HT, as compared to both HT patients and HD, which, instead, showed a similar percentage of Breg cells. Following a specific stimulation with CpG, the percentages of Breg cells were increased in the whole sample of SSc patients (p<0,001) as well as in isolated SSc and in SSc+HT ones as compared to isolated HT. However, the qualitative analysis, obtained through the detection of IL-10 producing-phenotype, revealed that the percentage of CpG-stimulated CD24hiCD38hi-IL10+cells were significantly decreased in SSc patients (p<0.0001) with no difference between isolated SSc and SSc+HT patients. IL-10 producing-phenotype was instead slightly increased in HT patients as compared to HD (4.1 vs 2.8%). The presence of SSc seems to be characterized by an enrichment of total Breg cells but by a reduced Breg IL-10 producing-phenotype, representing functional Bregs. This last finding was entirely due to the presence of SSc independently from the association with HT. This behaviour is different from the ones described about the association of HT with organ-specific autoimmune disorders.